Sarana Pengaitan Kalimat dalam Teks Wacana Berita Kompas - Nazifa, Farah; Wardiana, Wardiana; Fadilla, Nur Aulia; Rahmadiana, Nisa; Lutfia, Haula; Sundana, Lina (Lingua Susastra, 2024)
The purpose of this study is to describe the means of linking sentences in discourse texts on Kompas daily news, as well as analyze its impact on readers' understanding. The type of research used is descriptive qualitative, with data collection techniques through thorough reading of news texts, rewriting relevant texts, classification, and analysis. The researcher obtained data from three news discourse texts. The first news contains six data: 3 pronouns, 1 word equivalent, 1 conjunction, and 1 common theme. The second news has ten data: 1 pronoun, 2 word equivalents, 4 conjunctions, 1 common theme, 1 designation, and 1 opposite word. The third news story includes three data: 1 pronoun and 2 conjunctions. Based on the analysis, the discourse text in Kompas news shows a good and correct use of linking means, thus structuring the discourse text to be more structured and easy to understand.